2019
DOI: 10.1111/sifp.12093
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Two Quality of Care Measures: Results from a Longitudinal Study of Reversible Contraceptive Users in India

Abstract: Bruce's quality of care framework, developed nearly three decades ago, brought needed international attention to family planning services. Various data collection efforts exist to measure the quality of contraceptive services. Our study validates two process quality measures and tests their predictive validity related to contraceptive continuation among 2,699 married women who started to use a reversible contraceptive method in India. We assessed four process quality domains with 22 items, which were reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…Measures of quality were broken down into four domains of process quality (Jain, Townsend & Ramarao 2018;Jain et al 2019a):…”
Section: Quality Of Care Received At Enrollmentmentioning
confidence: 99%
“…Measures of quality were broken down into four domains of process quality (Jain, Townsend & Ramarao 2018;Jain et al 2019a):…”
Section: Quality Of Care Received At Enrollmentmentioning
confidence: 99%
“…A seven-country study of health insurance schemes (Ross et al, 2018) concluded that despite the formal inclusion of FP services in the national benefits packages examined, actual integration of these services faced challenges, with implications for the availability of FP services in practice. A study in India also found that use of FP under the national health insurance scheme was low, estimated at 2%, with poorer families less likely to know of its inclusion (Mozumdar et al, 2019).…”
Section: Package: What To Purchasementioning
confidence: 99%
“…There are many tools to assess the quality of FP services, however, there is lack of agreement on their routine use (Sprockett 2017). Recent studies have validated quality measures appropriate for routine reporting in FP service delivery settings, finding that higher values on the FP quality measures were associated with increased contraceptive use and reduced discontinuation (Jain et al, 2013;Jain and Winfrey, 2017;Chakraborty et al, 2019;Jain et al, 2019;Holt et al, 2019). While the evidence and the validated metrics are promising, measurement of rights such as client autonomy in service delivery settings can be further improved (Bertrand et al, 2014;Cole et al, 2019).…”
mentioning
confidence: 99%
“…However, tools that attempt to systematically measure the quality of FP care based on client report rarely focus on the dimensions of individuals' experiences with counseling [ 2 ]. Only a few existing tools designed to measure the quality of contraceptive counseling have assessed for reliability and validity in low- and middle-income countries (LMICs) [ 8 , [12] , [13] , [14] ]. Sudhinaraset et al, developed and validated the Person-Centered Family Planning scale in India and Kenya as a 20- or 22-item measure capturing two primary domains: autonomy, respectful care and communication; and health facility environment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sudhinaraset et al, developed and validated the Person-Centered Family Planning scale in India and Kenya as a 20- or 22-item measure capturing two primary domains: autonomy, respectful care and communication; and health facility environment [ 14 ]. Jain et al developed and validated a contraceptive care measure in India, both a longer 22-item and shorter 10-item form, capturing information exchange and interpersonal relations between provider and client on four domains: respectful care, method selection, effective use of method selected and continuity of contraceptive care [ 12 ]. Holt et al, developed and validated the Quality of Contraceptive Counseling scale in Mexico as a 22-item measure of FP client experiences with providers, focusing on three domains: information exchange, interpersonal relationship and disrespect/abuse [ 13 ].…”
Section: Introductionmentioning
confidence: 99%